Validated High Performance Liquid Chromatographic Method for Simultaneous Determination of Rosiglitazone, Cilostazol, and 3,4-Dehydro-cilostazol in Rat Plasma and its Application to Pharmacokinetics - Varanasi, VS Kanthi Kiran; Veeraraghavan, Sridhar; Potharaju, Suresh; Thappali, RS Satheeshmanikandan; Raghavan, Rashmi; Vakkalanka, VS Swaroop Kumar (Arzneimittelforschung, 2008)
A high performance liquid chromatographic (HPLC) method for simultaneous determination of rosiglitazone, CAS 122320-73-4, RSG), cilostazol (CAS 73963-72-1, CLZ) and its active metabolite 3, 4-dehydro-cilostazol (DCLZ), using pioglitazone (PIO) as internal standard (IS), in rat plasma is described. The plasma was extracted with methyl t-butyl ether, the dry extract was reconstituted in mobile phase and the aliquot was injected. The eluent drugs were detected by UV at dual wavelength of 226 nm (RSG and DCLZ) and 257nm (CLZ). The mobile phase consisting of acetonitrile:potassium di-hydrogen phosphate buffer (35:65 v/v) was used at the flow rate of 1.2 ml/min on a reverse phase C18 column. The absolute recovery was above 90 % of all analytes over the concentration range of 25-2500 ng/ml for RSG and CLZ and 20-2000 ng/ml for DCLZ. The relative standard deviation (RSD) of the inter-day and intra-day precision ranged from 2.8 to 8.4 % and 0.9 to 5.9 %, respectively. The method is simple, rapid, accurate and sensitive and was applied to pharmacokinetic studies.
Keywords: Antidiabetics; CAS 73963-72-1; CAS 122320-73-4; Cilostazol, determination in rat plasma, HPLC-UV, pharmacokinetics; 3, 4-Dehydro-cilostazol, determination in rat plasma, HPLC-UV, pharmacokinetics; Drug-drug interactions; Rosiglitazone, determination in rat plasma, HPLC-UV, pharmacokinetics